การถ่ายทอดความคิดเรื่องจิตวิญญาณในภาพยนตร์ - พึงพิศ เทพปฏิมา (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To analyze, describe the concept of the spirituality and the transmission of the concept of the spirituality in films and also to study the presentation of the situation of the spirituality in the society through the concept of spirituality in films. This study is the qualitative research, which analyze the content of the films that were showed in the theatres in Thailand during 2001 and June 2003. There are 11 films which have the contents of the concept of spirituality in films are obviously seen. There are 7 of the Hollywood films and 4 of the Thai and Asian films. These are analyzed through the narrative structures of the films which are divided into 7 categories together with the analyze of the documentary which are the story in brief and the articles about the film. The result of the study is that the Hollywood films and the Thai and Asian films have transmitted the concept of the spirituality in the same criteria: the faith and belief in God and certain gods, the search of the truth or any facts of life, the confirmation of the ethics and human s consciousness between right and wrong, the thought of the materialism in the present time, the sacrifice and the confirmation of human love & lust. The study reveals that there is no difference between these two types of film in terms of the concept of spirituality. The structures of the storytelling of the films which are mostly used are the conflict and the character. The study of the presentation of the situation of the spirituality in the society in the films shows that the Hollywood films have primarily reflected the context in the society through culture and economy & technology, whereas the Thai and Asian films have mainly reflected the context in the society through culture.